2001
DOI: 10.1006/dbio.2000.0129
|View full text |Cite
|
Sign up to set email alerts
|

Two Sox9 Genes on Duplicated Zebrafish Chromosomes: Expression of Similar Transcription Activators in Distinct Sites

Abstract: Sox9 is a transcription factor required for cartilage formation and testis determination in mammals. We have cloned from zebrafish two sox9 genes, termed sox9a and sox9b. Gene phylogenies showed that both genes are orthologous to tetrapod SOX9 genes. Genetic mapping showed that these two loci reside on chromosome segments that were apparently duplicated in a large-scale genomic duplication event in ray fin fish phylogeny. Both Sox9a and Sox9b proteins bind to the HMG consensus DNA sequences in vitro. We tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
283
2
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(324 citation statements)
references
References 61 publications
25
283
2
2
Order By: Relevance
“…Our analysis shows that Sox genes of Tor douronensis (Sox4, Sox9, Sox14 and Sox21) have 2 to 4 copies compared to mammals, and the pattern was also observed in other teleost fishes [4,5,43] . A large number of duplicated copies of single copy mammalian genes have been identified in teleost fishes.…”
Section: The Evolution Of Sox Genes In Vertebrates and Fish-specific supporting
confidence: 72%
“…Our analysis shows that Sox genes of Tor douronensis (Sox4, Sox9, Sox14 and Sox21) have 2 to 4 copies compared to mammals, and the pattern was also observed in other teleost fishes [4,5,43] . A large number of duplicated copies of single copy mammalian genes have been identified in teleost fishes.…”
Section: The Evolution Of Sox Genes In Vertebrates and Fish-specific supporting
confidence: 72%
“…As for teleosts, it was reported that two types of Sox9 were reported as Sox9a and Sox9b/a2 (Zebrafish, Chiang et al, 2001;medaka, Nakamoto et al, 2005). However, testisdominant type of Sox9 was different in each species (Zebrafish, tilapia, Sox9a; medaka, Sox9b/a2).…”
Section: Discussionmentioning
confidence: 99%
“…SOX9, the direct target of Sry, plays a critical role in testis determination in mammals (Foster et al 1994). Two SOX9 genes, termed SOX9a and SOX9b, have been identified in zebrafish (Chiang et al 2001), but whether SOX9a and/or SOX9b are involved in sex determination or differentiation has so far not been studied . In orangespotted groupers, we cloned a 252 bp fragment of SOX9 and produced a specific antibody.…”
Section: Molecular Mechanisms On Sex Change In Groupersmentioning
confidence: 99%